2023
DOI: 10.1093/cercor/bhac502
|View full text |Cite
|
Sign up to set email alerts
|

Speech onsets and sustained speech contribute differentially to delta and theta speech tracking in auditory cortex

Abstract: When we attentively listen to an individual’s speech, our brain activity dynamically aligns to the incoming acoustic input at multiple timescales. Although this systematic alignment between ongoing brain activity and speech in auditory brain areas is well established, the acoustic events that drive this phase-locking are not fully understood. Here, we use magnetoencephalographic recordings of 24 human participants (12 females) while they were listening to a 1 h story. We show that whereas speech–brain coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…We confirmed that temporally manipulating prosodic cues compromises cortical alignment to speech, specifically in bilateral auditory areas in the delta frequency band (Fig 2A-B). This replicates previous EEG findings [39], aligns with a proposed role of delta oscillations in temporal expectations [55,56] and is consistent with previous speech-brain coupling research proposing delta activity specific to speech onsets [23]. In this line, we foster the notion that delta speech-brain coupling reflects top-down predictive processes [15] evoked by acoustical regularities [57,58]; in particular the temporal structure of pauses [46].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We confirmed that temporally manipulating prosodic cues compromises cortical alignment to speech, specifically in bilateral auditory areas in the delta frequency band (Fig 2A-B). This replicates previous EEG findings [39], aligns with a proposed role of delta oscillations in temporal expectations [55,56] and is consistent with previous speech-brain coupling research proposing delta activity specific to speech onsets [23]. In this line, we foster the notion that delta speech-brain coupling reflects top-down predictive processes [15] evoked by acoustical regularities [57,58]; in particular the temporal structure of pauses [46].…”
Section: Discussionsupporting
confidence: 91%
“…While memory limits constrain chunk duration and thus necessitate occasional segmentation, each chunk-size filling of the buffer is coherent through the inter-word dependencies—thus allowing for the integration of word meanings within the chunk, and thus comprehension [43]. Previously, invasive work has shown that a spatially distinct area within superior temporal gyrus is exclusively sensitive to speech onsets [51] while non-invasive recordings demonstrated that delta speech-brain coupling is specific – and temporally restricted - to speech onsets [23]. However, it is not yet clear whether contextually-driven onsets (such as the boundaries of multi-word chunks) are sufficient to align activity on longer time-scales during listening.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the acoustic signal is reduced to an overall feature that best represents the auditory stimulus. The envelope and/or its derivative has been a strong candidate as a way to capture overall capture naturalistic speech (Chalas et al, 2023) and music (Di Liberto et al, 2020;Dmochowski et al, 2012;Hausfeld et al, 2021;Kaneshiro et al, 2020;Weineck et al, 2022).…”
Section: Stimulus-response Correlationmentioning
confidence: 99%
“…Such investigations have been conducted in brain oscillations (Chalas et al, 2023;Harding et al, 2019;Kaneshiro et al, 2020;Peelle et al, 2013;Vanden Bosch der Nederlanden et al, 2020); thought questions remain to what extent this could apply also to peripheral rhythms (Criscuolo et al, 2022;Klimesch, 2018;Parviainen et al, 2022).…”
Section: Stimulus-response Phase Coherencementioning
confidence: 99%
See 1 more Smart Citation